Sub graph sampling and case citation network: a case study - Khanam, Nidha; Sunil Wagh, Rupali (International Journal of Engineering and Technology, 2018)
Graphs or networks very commonly are used to represent connected or linked data. With the penetration of www in every sphere of life networked relationships can be easily established through communication links over web and network and graph analysis come as obvious choices of data representation and analysis. There are processes which can be analysed as network not through web but through the knowledge links available in these domains. In both these cases network analysis is challenged by the enormous size of the network in terms of nodes and links. Sub graph sampling can effectively be employed on large network structures to reduce the size of data while preserving the original properties of the network. Through this paper authors present a case study on application of sub graph sampling approach to obtain reduced case citation network in legal domain.Â Â